Thermodynamic consideration of the retention mechanism in a poly(perfluoroalkyl ether) gas chromatographic stationary phase used in packed columns - Castells, R. C. (1996)
Retention voluntes of fifteen hydrocarbons were measured in columns containing several concentrations of a commercial poly(perfluoroalkyl ether), Fomblin Y HVAC 140/13, as the stationary phase. Two different type ofpacking were studied: one ofthem employed pre-silylated Chromosorb P AW DMCS as the solid support, and the other type wasprepared by coating the stationary phase on Chromosorb P AW and silylating on-column. On-column silylated columns showed unequivocal symptoms of partial deactivation; retention volumes changed regularly with the contení of stationary phase in pre-silylated columns. Analysis of retention in pre-silylated columns indicates that a mixed mechanism (partition and adsorption on the gas-liquid interface) is operative. Systems hydrocarbon + perfluorocompound show pronounced positive deviations from the ideal behaviour that can be attributed to repulsión between the hydrocarbon and the perfluorocompund segments.